175. Antibiotic Resistance in Select Gram-negative Bacteria Over the Past Decade Among Hospitalized Veterans Nationally. (4th December 2021) - Xin Liao, J; Lopes, Vrishali; Appaneal, Haley J; LaPlante, Kerry; Caffrey, Aisling
Abstract: Background: Public health institutions including the World Health Organization and the United States Centers for Disease Control and Prevention (CDC) have recognized the threat of antibiotic resistant infections caused by Gram-negative bacteria. These bacteria are particularly concerning as they can demonstrate resistance to all available antibiotic classes through various mechanisms. We set out to assess antibiotic resistance trends in Gram-negative bacteria to optimize antimicrobial stewardship and infection control initiatives in our health system. Methods: We identified positive cultures (1st per patient per month) of P. aeruginosa and select Enterobacterales ( Citrobacter, Escherichia coli, Enterobacter, Klebsiella, Morganella morganii, Proteus mirabilis, Serratia marcescens ) collected from patients hospitalized at Veterans Affairs (VA) Medical Centers nationally from 2011 to 2020. Time trends were assessed with joinpoint regression to estimate average annual percent changes (AAPC) with 95% confidence intervals (CIs) for the following resistance phenotypes utilizing CDC definitions: multi-drug resistance (MDR), extended-spectrum beta-lactamase (ESBL), and carbapenem (CR) and fluoroquinolone (FR) resistance. Results: We included 496, 384 isolates in our study: E. coli (32.6%), Klebsiella (20%), P. aeruginosa (18.9%), P. mirabilis (11.5%), Enterobacter (7.8%), Citrobacter (3.7%), S. marcescens (2.9%), and M. morganii (2.6%). Trends in resistance are shown in the figures. MDR, ESBL, CR, and FR decreased significantly (p< 0.05) over the study period for most of the organisms assessed, with the exception of MDR and ESBL E. coli and CR P. mirabilis which remained stable, and CR M. morganii which increased significantly by 7.1% per year (95% CI 0.2% to 14.5%). The largest decreases were in CR E. coli by 29.5% per year (95% CI -36.5% to -21.8%), CR Klebsiella by 23.7% per year (95% CI -27.6% to -19.5%), and MDR and CR S. marcescens by 12.2% (95% CI -14.4% to -9.9%) and 12.3% per year (95% CI -16.2% to -8.1%), respectively. Figure 1. Antibiotic resistance trends in Citrobacter spp., E. coli, Enterobacter spp., and Klebsiella spp. Antibiotic resistance trends (by percentage) in (a) Citrobacter spp, (b) E. coli, (c) Enterobacter spp, and (d) Klebsiella spp from 2011-2020. Abbreviations: MDR = multi-drug resistance (defined as non-susceptible to at least 1 drug in at least 3 of the following categories: extended-spectrum cephalosporins, fluoroquinolones, aminoglycosides, carbapenems, piperacillin/tazobactam); ESBL = extended spectrum beta-lactamase (defined as non-susceptible to at least 1 of the following drugs: cefepime, ceftriaxone, cefotaxime, ceftolozane/tazobactam, ceftazidime/avibactam); CR = carbapenem resistance (defined as non-susceptible to at least 1 carbapenem); FR = fluoroquinolone resistance (defined as non-susceptible to at least 1 fluoroquinolone); AAPC = annual average percentage change; CI = confidence interval. Figure 2. Antibiotic resistance trends in Pseudomonas aeruginosa, Proteus mirabilis, Serratia marcescens, and Morganella morganii . Antibiotic resistance trends (by percentage) in (e) Pseudomonas aeruginosa, (f) Proteus mirabilis, (g) Serratia marcescens, and (h) Morganella morganii from 2011-2020. Abbreviations: MDR = multi-drug resistance (defined as non-susceptible to at least 1 drug in at least 3 of the following categories: extended-spectrum cephalosporins, fluoroquinolones, aminoglycosides, carbapenems, piperacillin/tazobactam); ESBL = extended spectrum beta-lactamase (defined as non-susceptible to at least 1 of the following drugs: cefepime, ceftriaxone, cefotaxime, ceftolozane/tazobactam, ceftazidime/avibactam); CR = carbapenem resistance (defined as non-susceptible to at least 1 carbapenem); FR = fluoroquinolone resistance (defined as non-susceptible to at least 1 fluoroquinolone); AAPC = annual average percentage change; CI = confidence interval. Conclusion: Overall, MDR, ESBL, CR, and FR in Enterobacterales and P. aeruginosa decreased from 2011 to 2020 in the VA. These results may be related to the robust infection control and antimicrobial stewardship programs instituted among VA Medical Centers nationally. Disclosures: Kerry LaPlante, PharmD, Merck (Research Grant or Support)Pfizer Pharmaceuticals (Research Grant or Support)Shionogi, Inc (Research Grant or Support) Aisling Caffrey, PhD, Merck (Research Grant or Support)Pfizer (Research Grant or Support)Shionogi, Inc (Research Grant or Support)